Preoperative Multimodal Prehabilitation and Surgical Outcomes in Ovarian Cancer Cytoreduction: A Systematic Review - Vegy Supriadi; Hacantya Pradipta; Gatot Nyarumenteng Adhipurnawan Winarno (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Cytoreductive surgery for ovarian cancer imposes substantial physiological stress and is associated with high postoperative morbidity, particularly in patients with advanced disease. Multimodal prehabilitation has been proposed to optimize the preoperative condition, but its effectiveness in ovarian cancer remains uncertain.Objective: This study aims to evaluate the effects of multimodal prehabilitation on perioperative outcomes, functional capacity, and oncologic recovery in women undergoing cytoreductive surgery for epithelial ovarian cancer.Methods: A systematic review was conducted following PRISMA guidelines. PubMed, Cochrane Library, and ScienceDirect were searched for studies assessing multimodal prehabilitation prior to ovarian cancer surgery. Eligible studies included observational and interventional designs reporting functional, perioperative, or oncologic outcomes. Data were synthesized narratively.Results: Five studies (2022–2025) were included. Prehabilitation consistently improved preoperative functional capacity. Effects on postoperative complications and intensive care use were inconsistent; however, some studies reported shorter hospital stays and earlier initiation of adjuvant chemotherapy. All studies had a moderate risk of bias.Conclusion: Multimodal prehabilitation may enhance functional capacity and support recovery, but current evidence remains limited. Further high-quality randomized trials are needed.Prehabilitasi Multimodal Praoperatif dan Luaran Bedah pada Sitoreduksi Kanker Ovarium: Sebuah Tinjauan SistematisAbstrakPendahuluan: Pembedahan sitoreduktif pada kanker ovarium menimbulkan stres fisiologis yang signifikan dan berisiko tinggi menyebabkan morbiditas pascaoperasi, terutama pada pasien dengan penyakit stadium lanjut. Prehabilitasi multimodal telah dikembangkan untuk mengoptimalkan kondisi pasien sebelum operasi, namun efektivitasnya pada kanker ovarium masih belum jelas.Tujuan: Penelitian ini bertujuan mengevaluasi secara sistematis pengaruh prehabilitasi multimodal terhadap luaran perioperatif, kapasitas fungsional, dan pemulihan onkologis pada pasien yang menjalani bedah sitoreduksi kanker ovarium epitel.Metode: Tinjauan sistematis dilakukan sesuai pedoman PRISMA. Pencarian literatur dilakukan pada PubMed, Cochrane Library, dan ScienceDirect untuk studi yang mengevaluasi prehabilitasi multimodal sebelum operasi kanker ovarium. Studi observasional dan intervensional yang melaporkan luaran fungsional, perioperatif, atau onkologis diikutsertakan. Data disintesis secara naratif.Hasil: Setelah dilakukan tinjauan lima studi antara tahun 2022-2025. Prehabilitasi secara konsisten meningkatkan kapasitas fungsional praoperasi. Dampaknya terhadap komplikasi pascaoperasi dan penggunaan perawatan intensif masih bervariasi, namun beberapa studi melaporkan penurunan lama rawat inap dan percepatan inisiasi kemoterapi adjuvan. Seluruh studi memiliki risiko bias sedang.Kesimpulan: Prehabilitasi multimodal berpotensi meningkatkan kapasitas fungsional dan mendukung pemulihan pascaoperasi, namun bukti yang ada masih terbatas. Diperlukan uji acak terkontrol dengan desain yang lebih baik.